Conceptions on pharmaceutical services in Brazilian primary health care - Costa, Ediná Alves (Rev Saude Publica, 2017)
OBJECTIVE: To identify and discuss the conceptions of pharmaceutical services in Brazilian Primary Health Care, according to different subjects. METHODS: This study is part of the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos – Serviços, 2015 (PNAUM – National Survey on Access, Use and Promotion of Rational Use of Medicines – Services, 2015), which is composed of an information survey in a representative sample of cities, stratified according to Brazilian regions, and a subsample of primary health care services. Municipal secretaries of health, those responsible for pharmaceutical services, and those responsible for medicine delivery in pharmacies/dispensing units of the selected services were interviewed. The questionnaires included one question about the understanding of the interviewee regarding pharmaceutical services. The content analysis technique was used to apprehend, in the statements, the meanings attributed to pharmaceutical services, which were subsequently classified into categories according to their main conceptions. RESULTS: Among the wide diversity of conceptions on pharmaceutical services (PS), we highlight the ones focused on 1) logistic control of medicines with activities concerning guidance or information on their use and 2) guidance or information to users on the use of medicine. The findings reveal a shifting tendency from a medicine-focused conception to one that considers the users and their needs as the final recipient of these actions. However, the lack of references to conceptions regarding care management and integrality point out the slowness of this change; after all, this is a social and historical process that comprises the production of meanings that transcend legal, logistic, and technical arrangements in pharmaceutical services. CONCLUSIONS: The diversity of conceptions expresses the several meanings attributed to pharmaceutical services; we also identified, in their reorientation process, a movement that reflects a gradual shift in the technical paradigm, from the focus on medicine logistics to a user-oriented approach of health services.